South-South Cooperation and Knowledge Exchange : A Perspective from Civil Society - Cruz, Anabel (2012)
South-South cooperation is not new. It has been around for several decades in the form of economic integration, cultural exchanges, and technical cooperation. Traditional North-South cooperation, however, with resources coming from the rich northern countries to the poor southern ones has been supplemented by other models. Indeed, middle income countries have been taking on various roles, not only as recipients of development aid, but also as providers of development cooperation. New actors and approaches have entered the development cooperation landscape.